2021
DOI: 10.2174/1389200221666200523155617
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Drug Resistance by Platonia insignis Mart. Extract, Ethyl Acetate Fraction and Morelloflavone/Volkensiflavone (Biflavonoids) in Staphylococcus aureus Strains Overexpressing Efflux Pump Genes

Abstract: Background: Microbial resistance to antibiotics is a global public health problem, which requires urgent attention. Platonia insignis is a native species from the eastern Brazilian Amazon, used in the treatment of burns and wounds. Objectives: To evaluate the antimicrobial activity of the hydroalcoholic extract of P. insignis (PIHA), the ethyl acetate fraction (PIAE), and its subfraction containing a mixture of biflavonoids (BF). Moreover, the effect of these natural products on the antibiotic activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Despite not showing activity against this specific strain, addition of these compounds to the growth medium at 256 μ g/mL (MIC 1/4) potentiated the antibacterial effect of norfloxacin against the SA-1199B strain, reducing the MIC values for norfloxacin by at least two-fold ( Table 1 ). Modulating effect on the resistance to norfloxacin could be explained by inhibition of NorA efflux pump overproduced by SA-1199B, as already reported for several compound classes, such as alkamides [ 18 ], chalcones [ 44 46 ], flavonoids [ 47 50 ], and lignans [ 51 ]. In fact, visnagin, and khellin showed a modulating effect like that exhibited by the known NorA inhibitor chlorpromazine.…”
Section: Resultsmentioning
confidence: 60%
“…Despite not showing activity against this specific strain, addition of these compounds to the growth medium at 256 μ g/mL (MIC 1/4) potentiated the antibacterial effect of norfloxacin against the SA-1199B strain, reducing the MIC values for norfloxacin by at least two-fold ( Table 1 ). Modulating effect on the resistance to norfloxacin could be explained by inhibition of NorA efflux pump overproduced by SA-1199B, as already reported for several compound classes, such as alkamides [ 18 ], chalcones [ 44 46 ], flavonoids [ 47 50 ], and lignans [ 51 ]. In fact, visnagin, and khellin showed a modulating effect like that exhibited by the known NorA inhibitor chlorpromazine.…”
Section: Resultsmentioning
confidence: 60%
“…To verify if the modulating effect is related with efflux pump inhibition, assays were performed replacing Norfloxacin by EtBr. As the only known mechanism of bacterial resistance to EtBr is mediated by efflux pumps (Markham et al 1999 ), this DNA-intercalating dye have been used to evaluate the potential efflux pump inhibitory activity of natural products (Silva et al 2021a ), isolated phytochemicals (Silva et al 2021b ) and synthetic compounds (Faillace et al 2021 ; Costa et al 2016 ). Results showed that EOPC was also able to modulate the resistance to EtBr in both SA1199B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The samples used to perform the biological assays, hydroalcoholic extract (EHPi), ethyl acetate fraction (FAcOEt) and biflavonoids mixture (MB) were obtained by developing the work of Silva et al [ 16 ], performed in the Laboratory of Organic Geochemistry of the Federal University of Piauí (LAGO/UFPI). The flowers of Platonia insignis Mart.…”
Section: Methodsmentioning
confidence: 99%
“…In our group, Silva et al [ 16 ] isolated and identified a mixture of two biflavonoids (moreloflavone and volkensiflavone) and a polyisoprenylated benzophenone garcinielliptona FC (GFC) from the hydroalcoholic extract of P. insignis flowers. These compounds have proven to be responsible for important pharmacological activities attributed to the species.…”
Section: Introductionmentioning
confidence: 99%